TROPRO impact assessment (June 1993 to June 1995) - Nurse, James O.J. (TROPRO Christ ChurchBB, 1995)
Presents the background and evaluation of the West Indies Tropical Produce Support Project (TROPRO). Summarizes the findings of two surveys and contains the analysis of non-traditional exports. Presents conclusions and recommendations.